American pastoral - Roth, Philip, 1933-2018 (Vintage Books, 1997)
In American Pastoral, Philip Roth gives us a novel of unqualified greatness that is an elegy for all the twentieth century's promises of prosperity, civic order, and domestic bliss. Roth's protagonist is Seymour 'Swede' Levov - a legendary high school athlete, a devoted family man, a hard worker, the prosperous inheritor of his father's Newark glove factory - comes of age in thriving, triumphant post-war America. And then one day in 1968, Swede's beautiful American luck deserts him. For Swede's adored daughter, Merry, has grown from a loving, quick-witted girl into a sullen, fanatical teenager - a teenager capable of an outlandishly savage act of political terrorism. And overnight Swede is wrenched out of the longed-for American pastoral and into the indigenous American berserk.